Split-Ticket Voting in an STV System: Choice in a Non-Strategic Context. Issue 2 (2nd April 2016) - Marsh, Michael; Plescia, Carolina
Abstract : This article explores the sources of weak party-voting patterns in Irish elections, conceptualising this as split-ticket voting. Ireland provides a context where election results show split-ticket voting is common, but the strategic interpretations of such behaviour that have been very prominent elsewhere are not generally applicable. We employ data from the Irish national election studies to explore the behaviour of individuals embedded in a variety of contexts. The results demonstrate the prevalence of split-ticket voting, and they support the validity of non-strategic explanations. One source of explanation for the patterns we find lies in differences between individuals: partisanship and the extent to which voters are attracted to candidates rather than parties are important. A second source is contextual: the factors connected with the complexity of the choice facing voters have a powerful influence on split-ticket voting.